2007
DOI: 10.1016/j.pain.2007.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in self-perceived role identity modulate pain perception

Abstract: Pain is an experience including physiological and psychological factors. We assume that emotions may be elicited and increased through self-perceived role identity and that change of role identity alters quality and intensity of pain perception. We used role-play strategies to assess whether pain can be better tolerated whenever, in an unavoidable and unpleasant context, role identity confers pain a meaningful and thus suitable character. We induced antithetic roles in 21 actors who received heat stimuli on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
0
10
1
Order By: Relevance
“…Finally, the larger PR may also relate to differences in placebo interventions. Indeed, hero role playing induced modulation of selfperception has been demonstrated to increase heat pain tolerance in healthy adults (47).…”
Section: Placebo Analgesia Responsesmentioning
confidence: 99%
“…Finally, the larger PR may also relate to differences in placebo interventions. Indeed, hero role playing induced modulation of selfperception has been demonstrated to increase heat pain tolerance in healthy adults (47).…”
Section: Placebo Analgesia Responsesmentioning
confidence: 99%
“…The obtained data with popular and lyrical singers do not corroborate the data obtained to general population (4) , which the mean of pain in women is higher than men, suggesting that singing itself may reduce the amount of reported pain in general to both genders. Other studies about pain point out men and women are different regarding pain coping, threshold, and tolerance, women had higher complaints and lower resistance (13)(14)(15) . Regarding predominant pains, the three most reported pains by popular singers were all proximal to larynx: sore throat (66%), pain to speak (41%), and neck pain (35%).…”
Section: Discussionmentioning
confidence: 95%
“…These data suggest proximal pain to larynx complaint are more resident in people reporting vocal problems and then pain next to the larynx region during the practice of singing might indicate the presence or predisposition to the urge of voice disturbances, and restricting singing activity. The presence of small voice deviation in a singer may bring big financial impact, shows and presentations canceled and restricting the professional exercise (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) . In the studied sample there was a big search for otolaryngologists and speech language pathologists due to vocal disturbances and a correlation between the searches with the presence of body pains (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that the perception of pain is closely related to people's emotional states (10) . In this study, it was found that, in 12 of the 13 surveyed pains, choral singers reported less bodily pain than the general population.…”
Section: Discussionmentioning
confidence: 99%